HUBUNGAN ANTARA INTIMASI DALAM KELUARGA DENGAN TINGKAH LAKU AGRESIF SISWA - Rahayu, Nike; ., Taufik; ., Nurfarhanah (Konselor, 2013)
Intimacy within the family is required for each family member. Reality in schools show that many students who lack the intimacy of the family. These conditions impact on student behavior, among others behave aggressively. This phenomenon needs to be revealed especially in relation to the child's relationship with his parents. for that, the purpose of this study is to describe the intimacy of the family and aggressive student behavior, and to test whether there is a relationship between intimacy in families with aggressive behavior of students. Findings showed that there was a negative relationship between intimacy in families with aggressive behavior of students. that is, the better intimacy in the family, the aggressive behavior of students getting lower, not good otherwise the intimacy of the family then aggressive behavior of students is increasing. Keyword: Intimacy, Aggressive Behavior